THE MONASTERY OF “NEW NEAMŢ” – THE SACRED RIVER THAT FLEW IN THE OCEAN OF ROMANIAN HISTORY - GUŢANU, Stela (Studia Universitatis Babes-Bolyai Musica, 2011)
Sacred music is a field of culture that comprises the essential human values, which are able to build and perfect the complex cultural undertaking of the human life; it is an emotional illustration of the spirit. Through the truth it embodies, sacred music aspires to reflect man’s secret, inner soul. This is a part of the people’s psychic and spiritual life, through the feelings and the attitudes that it transmits. Moldova’s spiritual history is irrevocably marked by an ancient, original musical art, incorporated into an infinite emotional scale. Monasteries – a testimony of the oldness and uninterrupted continuity of the Romanian life on Bassarabian lands, as well as of the ethnic, historical, geographical, political, linguistic and religious unity between the Bassarabian Romanians and the Romanians from the entire Romania – a unity that has been undividable, unalienable, visible, resilient, perennial and prodigious through the ages, until today. Founded in 1864 by the monks departed from the old Monastery in Neamţ, the new Monastery of “Noul Neamţ” (meaning New Neamţ) took over not only the designation of the oldest, richest monastic foundation in Moldova, but also the ancient traditions of this outstanding century-old cultural centre. The 30 Slavonic and Romanian manuscripts from the 14th -19th centuries that Father Andronic brought along from the Neamţ Monastery in 1861, on his arrival in Bassarabia, were the basis for the foundation of the Monastery’s Library, as well as for the setup of catalogue of manuscripts stored in this monastic settlement. The discovery and in-depth analysis of each manuscript have helped complete the lists of works created by the psalms, more or less notorious. Moreover, they have led to a better understanding of the religious musical life from the old Moldavian monastery, of the beginnings of choral singing. The importance of this fund of manuscripts lies in not only its musical and historic worth, but it also testifies the unity in musical culture of Romanians everywhere.